Effect on osseointegration of dental implants treated with carboxyethylphosphonic acid and functionalized with BMP-2: preliminary study on a minipig model - López-Valverde, Nansi; Aragoneses, Javier; Rodríguez, Cinthia; Aragoneses, Juan Manuel (Frontiers in Bioengineering and Biotechnology, 2023)
Rough titanium surfaces biofunctionalised by osteogenic proteins, such as BMP-2, have been shown to accelerate the osseointegration process and reduce waiting times for prosthetic loading. The preclinical study presented here compared the bone in contact with the implant and bone neoformation and density, between titanium (Ti) implants with conventional etched surface (SLA type), with others treated with carboxyethylphosphonic acid (CEPA) and bone morphogenetic protein 2 (BMP-2), after four weeks of implantation in the tibia of a minipig model. Sixteen implants (8 experimental and 8 control) of Ti-Al16-V4 with a tapered screw design and internal hexagonal connection were randomly inserted into the tibiae of 4 minipigs, four in each tibia. The experimental implants were treated with CEPA and BMP-2 and sterilized with gamma radiation (25 KG). The insertion torque was 40 N and primary stability was measured with the Osstell® device (ISQ 64±2.6). Five bone parameters were evaluated: bone in contact with the implant (BIC), bone in contact with the corrected implant (BICc), new bone formation (BV/TV), bone density between threads (BAI/TA) and peri-implant bone density (BAP/TA). A histomorphometric study was performed and the samples were digitized using Adobe Photoshop Cs6. Statistical analysis of the variables was performed using SAS 9.4. After a period of 4 weeks, no significant clinical signs were observed, and all implants were integrated. Light microscopy of the experimental group revealed a BIC with no signs of fibrous tissue, but with areas of ectopic new bone in the medullary space. Statistical analysis showed significant results for BIC and BICc (p = 0.0001 and p = 0.001, respectively). No statistical significance was found for the other parameters evaluated. Despite the limitations of this study, our results demonstrated that dental implant surfaces treated with CEPA and BMP-2 improve their biological response to osseointegration.